Komunikasi Efektif dalam Proses Pembelajaran - Ahmad Fahroni (Journal of Teacher Training and Educational Research, 2024)
Effective communication in learning is key to enhancing the quality of the teaching and learning process. However, various communication barriers often hinder interactions between teachers and students, making it challenging to achieve learning objectives. This article aims to examine the role of communication in the educational context, with a focus on teacher-student interactions. The study employs a library research approach to analyze relevant literature. The findings indicate that effective communication encompasses openness, empathy, supportiveness, positive attitudes, and equality, all of which contribute to creating an optimal learning environment. Open communication models, such as dialogical and persuasive approaches, can help students better understand learning materials. Additionally, the utilization of information technology and learning media enhances the success of communication in education. By paying attention to factors such as the communicator, the communicant, and the message, teachers are expected to create an interactive learning environment that supports the achievement of educational goals.